High Sensitivity CH4 and CO2 Gas Sensor Using Fiber Bragg Grating Coated with Single Layer Graphene - Irawan, Dedi; Saktioto; Dwi Hanto; Widiyatmoko, Bambang; Sutoyo (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2024)
This article outlines the development of a Fiber Bragg Grating (FBG) intended for use as a sensor for CH4 and CO2 gases. Following fabrication, the FBG was effectively treated with a layer of Graphene Material through a modified RF Sputtering process. This coating procedure involved introducing argon gas into the chamber and subjecting the FBG, securely held by two vacuum stages, to a temperature range of 27°C to 600°C by adjusting the power supplied to the cathode and anode, ranging from 0 to 125 Watts. Subsequently, the FBG was employed as a key sensing element within an experimental setup aimed at measuring gas concentrations within a confined space. The assessment involved analyzing the reflected signal of the FBG using an Optical Interrogator System, which demonstrated a shift in the Bragg wavelength of the reflected signal corresponding to varying gas concentrations. This study indicates promising outcomes for the Graphene-coated FBG as a gas sensor. The sensor’s sensitivity was evaluated based on the Bragg wavelength shift resulting from gas presence within the chamber. The Graphene-coated FBG exhibited sensitivities of 3.3 ppm for CH4 and 3.7 ppm for CO2, surpassing those reported in prior research efforts.